Global Trends and World Development Indicators: Synergy Trends of Key Global Trends: Global Gross Domestic Growth in Relation to Global CO2 Emissions, Global Electric Power Consumption, Global Population, and Global Schooling Index Data - Kaivo-oja Jari; Vehmas Jarmo; Luukkanen Jyrki (Serbia, 2025)
This article includes global synergy trend analyses based on the world development indicators published by the work bank. in order to understand globalization phenomena, it is good to understand global trends and the interactions between global trends. The empirical study is based on the World Bank global data sets of world development indicators. The synergy analysis method and tool were developed to analyze the synergy between two different trends, but it can be used to analyze simultaneously the synergy between three trends representing the three different dimensions of sustainable development. It is good for decision-makers to be aware - not only of the development of the trends themselves, but decision-makers should be aware also of the interactions between global trends. there may be positive, negative, or no synergy between trends. These three different forms of synergy are therefore always possible. that is why this study is important and interesting. The empirical research delivers synergy analysis results of global trends in relation to global GDP. The critical global synergy analyses are linked to (1) global co2 emission, trend, (2) a trend in global electric power consumption, (3) global population trends, (4) population density trends, and (5) two critical global schooling index numbers (global primary completion rate (GPCR) and gender parity index, GPI) trends. This analysis is a unique synergy analysis study and all reported results are for the first time published in this empirical synergy study. This study provides many new results about synergies, which are relevant for global policy-makers and especially for the World Bank and for the United Nations.
Proceedings of international conference: "SUSTAINABLE DEVELOPMENT CONFERENCE 2022"